As significações sobre o Programa Bolsa Família: um estudo com mulheres acompanhadas por Centros de Referência da Assistência Social de Fortaleza - Paula, Luana Rêgo Colares de (2010)
This research aimed to understand the meanings of the Bolsa Família Program (PBF) built by the women beneficiaries and their relation to the monitoring of the public from this program at the Reference Center for Social Assistance (CRAS). From the methodological point of view, the implementation of this research occurred after the insertion, between August and December 2009, on activities developed by two CRAS in Fortaleza and that were part of a project to benefit from the PBF. In all, ten women participated in the stage of empirical research. The fieldwork involved participant-observations, the use of individual questionnaires and conducting two focus groups with these women. The corpus analyzed founded sources on the field diaries, in the questionnaire responses and in the audio recordings of the focus groups. The data produced and transcripts were organized based on content analysis and interpreted in the light of the paradigm of the network of meanings. Thus, the survey had a theoretical category, "meaning process. Four empirical categories were defined: "The provisional nature of the PBF", "The benefit: its character, its use(s) and the conditions to receive it"; "The way to operationalize the PBF" and "The place of CRAS on monitoring of PBF beneficiary”. The results show that a number of issues are articulated and interfered in the production of meanings, such as aspects of the trajectory of each participant, historical conditions and ideological development of social policies and programs to transfer income in the country, recent changes in scenario of social welfare policy; meanings about PBF circulating in the social context, the institutional context of PBF and monitoring of beneficiary families, and the proper context of interaction research. Data analysis indicates that these meanings are expressive of the tension in the socio-political juncture, between the signs of lack and rights. The data also support the view that the relatively early stage of monitoring conducted limits its possibility to destabilize current meanings and to contribute to the creation and increased circulation of new meanings for the PBF. Nevertheless, the results show relationships between the context of follow-up investigation and production of meanings about the durability of the PBF and the gender issues raised in the discussion of ownership of women in the program. About the ownership of women in PBF, on the one hand, it was expressive the production of meanings that demonstrate the limitation of ownership in extending the power of women at home. Second, the meanings in this respect also highlight the historical subordination of women compared to men, emphasizing the importance of resizing power relationships. The results also highlight that, among the participants, there is a embrittlement of the sense of "way out" of PBF bound to Complementary Programs.